Foreign historiography of Canadian troops' participation in the North Russia Intervention of 1918–1919 - A.V. Nerovnyi (Ученые записки Казанского университета: Серия Гуманитарные науки)
The analysis of the foreign historiography of Canadian troops' participation in the Allied Intervention to the North of Russia in 1918–1919 (also known as the Northern Russian Expedition, North Russia Intervention, etc.) has been performed in the paper. During the period of the Civil War and the Allied Intervention, Russia became a theater of military operations on the world scale. The vast territories were divided into a lot of fronts and zones of influence by the rival coalitions. Despite the fact that the main opposing forces in this war were the Red Army and the White Movement, other states also played an important political and military role in these events. The most active actors of the Allied Intervention are considered to be the United Kingdom and the United States of America. Under the conditions of the continuing World War, both of the powers contributed to the campaign, which spread at the territory of the former Russian Empire, a huge military contingent, a lot of weapons, ammunition and supplies, as well as significant amounts of money. However, the contribution of other participants in these events is overlooked by researchers. In addition to the British and Americans, the Allied Intervention was joined by French, Italian, Serbian, and Japanese contingents and other nations. It is noteworthy that the United Kingdom mobilized the units of its dominions (Canada, Australia and New Zealand) and colonies (India) for the military operation.